Biaxially stretched polyarylene sulfide-based resin film, laminate, circuit board, method for producing biaxially stretched polyarylene sulfide-based resin film, and method for manufacturing laminate
The biaxially stretched polyarylene sulfide resin film, modified by plasma treatment, addresses high-frequency transmission losses and adhesion issues by directly bonding with a smooth metal foil, resulting in a laminate with low loss and stable electrical properties.
Patent Information
- Application Number
- JP2023152242
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-09-20
- Publication Date
- 2025-04-02
AI Technical Summary
Existing circuit boards face issues with high transmission losses due to dielectric and conductor losses, particularly at high frequencies, and adhesion problems between polymer layers and metal foils, leading to instability and poor processing capabilities.
A biaxially stretched polyarylene sulfide resin film with controlled surface modifications through plasma treatment in an oxygen-containing atmosphere is used to bond directly with a smooth metal foil, ensuring strong adhesion without an adhesive, thereby reducing transmission losses and maintaining stable electrical properties.
The laminate achieves low transmission loss and excellent high-frequency circuit characteristics with strong adhesion, enabling stable impedance and accurate pattern processing, even at high temperatures.
Smart Images

Figure 2025044580000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a biaxially oriented polyarylene sulfide resin film, a laminate, a circuit board, a method for producing a biaxially oriented polyarylene sulfide resin film, and a method for producing a laminate, which can be suitably used for wiring board applications, circuit material applications, and the like. [Background technology]
[0002] With the development of communication technology and information processing technology, the electrical signals handled in the information and communications field are becoming faster and larger in capacity. To achieve faster and larger communication volumes, electrical signals are becoming higher in frequency, but since high-frequency electrical signals tend to have large transmission losses, circuit boards compatible with high frequencies are in demand. Transmission losses can be separated into dielectric loss and conductor loss, and it is necessary to reduce each of these losses.
[0003] Dielectric loss is proportional to the communication frequency, and the higher the frequency, the more susceptible it is to the effects of the dielectric loss, making it a particularly important factor in high-frequency communication. The dielectric loss is caused by the dielectric layer of the substrate, and the smaller the dielectric constant and dielectric dissipation factor of the dielectric layer, the smaller the dielectric loss. Therefore, as a material suitable for high-frequency substrates, attention has been focused on resins with small dielectric constants and dielectric dissipation factors, and a printed wiring board master sheet has been disclosed in which copper foil is bonded to a base film mainly composed of a liquid crystal polymer using an adhesive with a small average dielectric constant and average dielectric dissipation factor (Patent Document 1). Furthermore, wiring boards and laminates in which copper foil is directly heat-pressed onto a film without using an adhesive (Patent Documents 2 and 3) have also been disclosed. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2018-110193 A [Patent Document 2] JP 2006-179609 A [Patent Document 3] JP 2020-199707 A Summary of the Invention [Problem to be solved by the invention]
[0005] In Patent Document 1, a liquid crystal polymer with a small relative dielectric constant and dielectric dissipation factor is used to keep the dielectric loss low. The relative dielectric constant and average dielectric dissipation factor of the adhesive are also kept low, but there are problems with the dielectric properties deteriorating depending on the state of hardening of the adhesive, and the properties changing due to moisture absorption. In addition, it is not sufficient to obtain stable properties, such as a stable impedance being impossible due to unevenness in the in-plane thickness of the adhesive and deformation caused by interlayer stress differences generated by adhesive lamination.
[0006] In Patent Document 2, a laminate without adhesive is realized, but the surfaces of the polymer layer and the metal foil are roughened to ensure adhesion between the polymer layer and the metal foil. In high-frequency communication, the electrical signal is significantly affected by the skin effect, which concentrates on the surface of the conductor, so that a roughened conductor increases the effective transmission path length, resulting in large conductor loss.
[0007] Patent Document 3 discloses a laminate that ensures adhesion with a smooth surface without using an adhesive, but the adhesion is insufficient and the laminate is prone to peeling when etching thin wires that will become tracks, making it difficult to process thin tracks and reducing yields.
[0008] The present invention has been made in consideration of the above-mentioned circumstances, and an object of the present invention is to provide a laminate having low transmission loss, in which a resin film with excellent dielectric properties and a smooth copper foil are bonded together so as to have strong adhesion without the use of an adhesive. [Means for solving the problem]
[0009] A preferred embodiment of the present invention is as follows. (1) A biaxially stretched polyarylene sulfide resin film, characterized in that the ratio Fp / Fs of the sum of peak intensities Fp of fragments having ratios m / z of mass m to charge number z of 79.96, 96.96, and 155.99, respectively, among negative secondary ions obtained when at least one surface is analyzed by time-of-flight secondary ion mass spectrometry (TOF-SIMS), to the sum of peak intensities Fs of fragments having ratios m / z of 139.98 and 216.00, respectively, is 1.0 or more and 10.0 or less. (2) The biaxially stretched polyarylene sulfide resin film according to (1), in which the ratio of oxygen to carbon atoms O / C obtained by analyzing at least one surface by X-ray photoelectron spectroscopy (XPS) is 0.1 or more and 0.3 or less. (3) The biaxially stretched polyarylene sulfide resin film according to (1) or (2), wherein at least one surface has a ten-point average roughness RzJIS of 0.05 μm or more and 3.0 μm or less. (4) The biaxially stretched polyarylene sulfide resin film according to any one of (1) to (3), having a melting point of 260° C. or higher. (5) The biaxially stretched polyarylene sulfide resin film according to any one of (1) to (4), which has a relative dielectric constant of 3.2 or less at a frequency of 10 GHz. (6) A laminate having a metal foil bonded to at least one surface of a biaxially oriented polyarylene sulfide resin film, characterized in that when the surface (α-surface) of the metal foil peeled off from the biaxially oriented polyarylene sulfide resin film that was in contact with the biaxially oriented polyarylene sulfide resin film is analyzed by time-of-flight secondary ion mass spectrometry (TOF-SIMS), the ratio Fp / Fs of the sum of peak intensities Fp of fragments having ratios m / z of mass m to charge number z of 79.96, 96.96, and 155.99, respectively, to the sum of peak intensities Fs of fragments having ratios m / z of 139.98 and 216.00, respectively, is 1.0 or more and 10.0 or less. (7) The laminate according to (6), wherein the biaxially stretched polyarylene sulfide resin film and the metal foil are adhered to each other with an adhesion strength of 4 N / cm or more. (8) The laminate according to (6) or (7), wherein the biaxially stretched polyarylene sulfide resin film has a melting point of 260° C. or higher. (9) The laminate according to any one of (6) to (8), wherein the main component of the metal foil is copper. (10) The laminate according to any one of (6) to (9), wherein the ten-point average roughness RzJIS of the surface of the metal foil is 0.05 μm or more and 2.0 μm or less. (11) The laminate according to any one of (6) to (10), wherein the laminate is processed into a microstrip line having a line length of 10 cm and an impedance of 50 Ω, and the high-frequency circuit characteristics are measured, and the insertion loss at a frequency of 6 GHz is less than 2 dB. (12) A circuit board comprising the laminate according to any one of (6) to (11). (13) A method for producing a biaxially stretched polyarylene sulfide-based resin film, in which a ratio Fp / Fs of the sum of peak intensities Fp of fragments having ratios m / z of mass m to charge number z of 79.96, 96.96, and 155.99, respectively, among negative secondary ions obtained when at least one surface is analyzed by time-of-flight secondary ion mass spectrometry (TOF-SIMS), to the sum of peak intensities Fs of fragments having ratios m / z of 139.98 and 216.00, respectively, is 1.0 or more and 10.0 or less, comprising a plasma treatment step of subjecting the biaxially stretched polyarylene sulfide-based resin film to a vacuum plasma treatment in an oxygen-containing gas atmosphere. (14) a plasma treatment step of subjecting the biaxially stretched polyarylene sulfide resin film to a vacuum plasma treatment in an oxygen-containing gas atmosphere; A method for producing a laminate, comprising: a bonding step of overlapping a surface of the vacuum plasma-treated biaxially stretched polyarylene sulfide resin film with a metal foil, and bonding the surfaces by heating and pressing the surfaces, A method for producing a laminate, characterized in that when the surface (α-surface) of the metal foil peeled off from the biaxially oriented polyarylene sulfide resin film that was in contact with the biaxially oriented polyarylene sulfide resin film is analyzed by time-of-flight secondary ion mass spectrometry (TOF-SIMS), the ratio Fp / Fs of the sum of peak intensities Fp of fragments having ratios m / z of mass m to charge number z of 79.96, 96.96, and 155.99, respectively, to the sum of peak intensities Fs of fragments having ratios m / z of 139.98 and 216.00, respectively, is 1.0 or more and 10.0 or less. (15) a plasma treatment step of subjecting the biaxially stretched polyarylene sulfide resin film to a vacuum plasma treatment in an oxygen-containing gas atmosphere; A method for producing a laminate, comprising a step of overlapping a surface of the vacuum plasma-treated biaxially stretched polyarylene sulfide resin film with a metal foil, and bonding the surfaces by heating and pressing, A method for manufacturing a laminate, characterized in that the laminate is processed into a microstrip line with a line length of 10 cm and an impedance of 50 Ω and the high-frequency circuit characteristics are measured, and the insertion loss at a frequency of 6 GHz is less than 2 dB. Effect of the Invention
[0010] According to the present invention, a laminate can be obtained in which strong adhesion is achieved by directly bonding a smooth metal foil and a film, and a circuit board with low loss and excellent characteristics can be obtained. [Brief description of the drawings]
[0011] [Figure 1] 1A and 1B are schematic cross-sectional views of a laminate according to the present invention, in which (a) shows an example of a configuration in which a metal foil is bonded to the surface on one side, and (b) shows an example of a configuration in which a metal foil is bonded to the surfaces on both sides. [Diagram 2] 1 is a schematic cross-sectional view showing an α-plane exposed by peeling off a metal foil from a laminate according to the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0012] The biaxially oriented polyarylene sulfide resin film and laminate of the present invention will be described in detail below with reference to the drawings.
[0013] The biaxially stretched polyarylene sulfide resin film is a film whose main component is a polyarylene sulfide resin. The main component means that the main component accounts for 80% by mass or more of the raw materials constituting the film. The biaxially stretched polyarylene sulfide resin film may be a single layer, or may be a laminate of two or more layers. The polyarylene sulfide resin is a homopolymer or copolymer having a repeating unit of -(Ar-S)-. Examples of Ar include units represented by the following formulas (1) to (11).
[0014] [ka]
[0015] Here, R1 and R2 are substituents selected from hydrogen, alkyl groups, alkoxy groups, and halogen groups, and R1 and R2 may be the same or different.
[0016] The repeating unit of the polyarylene sulfide resin is preferably a p-arylene sulfide unit represented by the above formula (1), and representative examples thereof include polyphenylene sulfide, polyphenylene sulfide sulfone, polyphenylene sulfide ketone, their random copolymers, block copolymers, and mixtures thereof. A particularly preferred p-arylene sulfide unit is a p-phenylene sulfide unit, from the viewpoint of film properties and economic efficiency. From the viewpoint of durability, dimensional stability, etc., it is preferable that the p-phenylene sulfide unit represented by the structural formula of the following formula (12) accounts for 75 mol% or more of the total repeating units, more preferably 80 mol% or more, and even more preferably 85 mol% or more.
[0017] [ka]
[0018] By making the polyarylene sulfide resin film biaxially stretched, the mechanical strength, flatness, and productivity can be improved and thickness unevenness can be reduced. When used in communication such as boards, stabilizing the flatness and thickness unevenness reduces the error in the impedance of the transmission line and the loss. As a method of biaxial stretching, a sequential biaxial stretching method (a stretching method combining stretching in one direction at a time, such as a method of stretching in the longitudinal direction and then in the transverse direction), a simultaneous biaxial stretching method (a method of stretching in the longitudinal direction and the transverse direction at the same time), or a combination of these methods can be used. Biaxial stretching can be confirmed by the average value of 4,300 or more of 10 measurements of a parameter (Q value) indicating the sharpness of the resonance of the polyarylene sulfide film, measured using a molecular orientation meter (MOA-6015, manufactured by Oji Scientific Instruments).
[0019] The biaxially stretched polyarylene sulfide resin film preferably has a melting point of 260°C or higher. The melting point can be measured from the temperature of the melting endothermic peak in a DSC chart obtained using a differential scanning calorimeter according to JIS K7121-1987. When a plurality of peak temperatures are observed, the peak temperature on the lower side is regarded as the melting point. When the melting point of the film is 260°C or higher, the heat resistance of the laminate is increased and it can withstand processing and use at high temperatures. The upper limit of the melting point is preferably 300°C or lower, taking into consideration the temperature to be raised for the purpose of softening in order to increase the adhesiveness with the resin when the metal foil is joined.
[0020] The polyarylene sulfide resin for making the melting point of the surface layer 260° C. or higher contains p-phenylene sulfide units at 80 mol % or more, more preferably 85 mol % or more, of 100 mol % of the repeating units of the polyarylene sulfide resin. By reducing the copolymerization units and increasing the ratio of p-phenylene sulfide units, a tough film with a high melting point and excellent heat resistance can be obtained.
[0021] The biaxially stretched polyarylene sulfide resin film preferably has a relative dielectric constant of 3.2 or less at 10 GHz. By setting the relative dielectric constant to 3.2 or less, it is preferable because the dielectric loss can be reduced. In order to set the relative dielectric constant to 3.2 or less, a resin composition with low polarizability is sufficient, and polyarylene sulfide resins have this characteristic. When other resins are copolymerized with the polyarylene sulfide resin, it is also preferable to have a structure with low polarity. The polyarylene sulfide resin composition may contain various additives such as antioxidants, heat stabilizers, antistatic agents, and antiblocking agents within a range that does not impair the effects of the present invention.
[0022] The biaxially stretched polyarylene sulfide-based resin film may contain a layer made of other resin. Examples of the resin constituting the laminate include, but are not limited to, polyimide resin, polyamide resin, polyether ether ketone, polyetherimide, polyamide imide resin, polyolefin resin such as polyethylene and polypropylene, polystyrene, polycarbonate, acrylic resin, urethane resin, fluororesin, polyester resin such as polyethylene terephthalate and polyethylene naphthalate, polyketone, epoxy resin, etc. In addition, two or more kinds selected from the above and polyarylene sulfide-based resins can be blended and used.
[0023] The ten-point average roughness Rz of at least one surface of the biaxially stretched polyarylene sulfide resin film is preferably 0.05 μm to 3.0 μm, more preferably 0.07 μm to 2.0 μm. The ten-point average roughness RzJIS of the surface is defined in JIS B 0601-2001. When RzJIS is 0.05 μm or more, the film can slide appropriately when wound into a roll, and the occurrence of scratches and wrinkles can be suppressed, which is preferable. When RzJIS is 3.0 μm or less, the wiring end is not roughened when the metal foil of the laminate is etched and patterned, and a fine pattern can be accurately processed.
[0024] The thickness of the biaxially stretched polyarylene sulfide resin film is not particularly limited, but from the viewpoint of film-forming property and processability, it is preferably from 2 μm to 300 μm, more preferably from 5 μm to 180 μm, and even more preferably from 25 μm to 150 μm.
[0025] Biaxially stretched polyarylene sulfide-based films are highly heat-resistant crystalline films with few functional groups on the surface, and therefore there was a problem in that the adhesion had to be improved when they were made into a laminate. In particular, in applications related to high-frequency communication, roughening the surface to improve adhesion by the anchor effect would result in poor pattern accuracy and poor transmission characteristics, so it was necessary to make the surface smooth and improve adhesion. As a result of intensive research, the inventors have modified the surface of a biaxially stretched polyarylene sulfide-based resin film and found a surface that can improve adhesion even if the surface is smooth. The details are explained below.
[0026] In a preferred embodiment of the biaxially stretched polyarylene sulfide resin film, the ratio Fp / Fs of the sum of peak intensities Fp of fragments having m / z of 79.96, 96.96, and 155.99, among negative secondary ions obtained by analyzing at least one surface by time-of-flight secondary ion mass spectrometry (TOF-SIMS), to the sum of peak intensities Fs of fragments having m / z of 139.98 and 216.00, is 1.0 or more and 10.0 or less.
[0027] <Measurement conditions> Measurement equipment: ION-TOF time-of-flight secondary ion mass spectrometer TOF.SIMS5 Primary ion species: Bi3 ++ Primary ion acceleration voltage: 25 kV Static neutralization: yes Secondary ion (detection ion) polarity: negative
[0028] The fragments obtained when biaxially stretched polyarylene sulfide film was analyzed by TOF-SIMS were determined to be SO3 at m / z=79.96 based on the resin composition and molecular weight. - , m / z=96.96 is SO4H -, m / z=155.99 is C6H4SO3 - m / z=139.98 is derived from C6H4S2 - , m / z=216.00 is C 12 H8S2 - It is presumed that the Fp / Fs is derived from the above. That is, the first three types of ions have a structure in which the sulfur part of the polyarylene sulfide structure is oxidized, and the latter two types of ions have no oxygen atoms and show a structure in which the resin is not oxidized. That is, the fragments of m / z=79.96, 96.96, and 155.99 represent products oxidized by the surface treatment described below, while the fragments of m / z=139.98 and 216.00 represent the structure of an unoxidized resin, and Fp / Fs represents the degree of surface modification. The Fp / Fs of the biaxially stretched polyarylene sulfide resin film surface is preferably 1.0 or more and 10.0 or less, and more preferably 3.5 or more and 8.0 or less. By making the Fp / Fs 1.0 or more, sulfur oxides that interact with the metal foil are generated, and strong adhesion can be obtained between the smooth film and the metal foil without using an adhesive. In particular, when oxidized to a sulfuric acid or sulfurous acid state, it is relatively stable and does not easily change, so it is a particularly preferable structure in the present application, which requires processing at high temperatures. By setting Fp / Fs to 10.0 or less, it is possible to suppress the weakening caused by the molecular chain scission due to excessive oxidation of the film surface or excessive treatment, and to maintain strong adhesion with the metal foil. In order to adjust Fp / Fs to an appropriate range and ensure sufficient strength, it is effective to include a large number of p-phenylene sulfide units in the repeating units of the polyarylene sulfide resin. An example of the ratio is that the p-phenylene sulfide units are 80 mol% or more out of 100 mol% of the repeating units of the polyarylene sulfide resin. When the ratio of p-phenylene sulfide is high, the structure has high symmetry and a rigid structure, resulting in a film with low molecular mobility. Therefore, even when heated to bond the metal foil, the sulfur oxide generated on the surface by the surface treatment described below does not penetrate inside due to thermal motion, etc., but exists on the film surface, and can efficiently interact with the metal foil. In addition, since the same structure exists at a high ratio, the treatment is not biased and proceeds uniformly.
[0029] The biaxially stretched polyarylene sulfide resin film has an atomic ratio O / C of oxygen atoms to carbon atoms of at least one surface, which is detected by X-ray photoelectron spectroscopy (XPS) analysis, of 0.10 or more and 0.30 or less. XPS is an analytical method in which soft X-rays are irradiated onto a sample surface in an ultra-high vacuum, photoelectrons emitted from the surface are detected by an analyzer, and elemental information on the surface can be obtained from the binding energy value of bound electrons in the material, information on the bonding state can be obtained from the energy shift of each peak, and even quantification can be performed using the peak area ratio. XPS analyzes a depth region corresponding to the length (mean free path) that photoelectrons can travel through the material, so surface information on the measured surface can be obtained. The atomic ratio O / C of oxygen atoms to carbon atoms on the film surface is preferably 0.10 or more and 0.30 or less, more preferably 0.10 or more and 0.20 or less. If the atomic ratio O / C is 0.10 or more, the functional groups generated in the biaxially oriented polyarylene sulfide film will increase the interaction with the metal foil, and adhesive strength can be obtained. By setting the atomic ratio O / C to 0.30 or less, surface weakening due to excessive oxidation can be suppressed, and adhesive strength can be increased.
[0030] The biaxially stretched polyarylene sulfide resin film can be obtained by vacuum plasma treatment in an oxygen-containing gas atmosphere. Plasma treatment is a method of modifying the surface by exposing the treated body to discharge obtained by applying a high voltage of DC or AC between a high voltage applying electrode and a counter electrode. Since the biaxially stretched polyarylene sulfide resin film has low polarity, it does not have sufficient interaction with the contacting layer, and there are problems such as poor coverage and adhesion, and various surface treatments have been used so far. The aim of the surface treatment is to increase the polarity of the film surface and improve wettability, and corona treatment and ozone treatment in the atmosphere have been widely used with the aim of introducing many oxygen atoms. However, when the treatment intensity is increased to increase the functional groups introduced to the film surface, there is a problem that the molecular chain is cut and weakened, the surface layer undergoes cohesive failure, and the adhesion is reduced. In particular, in the case of a film having a high melting point and high crystallinity, the reaction energy required for the introduction of functional groups is large, and the reaction cannot be started unless the treatment is strong. However, once the reaction has started, it progresses rapidly, and the molecular chain is easily cut, resulting in overtreatment. The inventors have therefore conducted extensive research and found that plasma treatment using a dielectric-coated electrode described below in an atmosphere mainly composed of oxygen-containing gas can suppress the weakening of the surface layer and obtain good adhesion to the metal foil. The vacuum plasma treatment is a treatment in which a high voltage is applied to activate the gas in the chamber and expose the film surface to the generated radicals and ions to modify the film surface. In general, inert gases such as argon and nitrogen are preferably used as the gas used in the reaction, but it has been found that in this system, it is preferable to introduce molecules containing oxygen at a high partial pressure. The method for producing a polyarylene sulfide resin film of the present invention will be specifically described below.
[0031] A preferred embodiment of the method for producing a polyarylene sulfide-based resin film is a plasma treatment of a biaxially stretched polyarylene sulfide-based resin film under reduced pressure. 2 More than 50,000W min / m 2It is preferable to include a step of performing plasma treatment at the following treatment power density. When performing plasma treatment under reduced pressure, the atmospheric pressure is preferably 0.1 Pa to 100 Pa, and more preferably 1 Pa to 50 Pa. By setting the pressure at 0.1 Pa or more, plasma discharge can be stably maintained, and active species having energy suitable for generating functional groups are present at an appropriate density, enabling efficient modification and stable treatment. By setting the pressure at 100 Pa or less, it is possible to suppress deactivation due to reaction between active species, and to provide a sufficient treatment effect to the treated object. From the same viewpoint, 50 Pa or less is more preferable.
[0032] In plasma processing, it is important to adjust the atmosphere by introducing gas into the discharge space in order to increase the processing efficiency or introduce specific functional groups. The gases used are argon, N2, He, Ne, O2, CO2, CO, air, water vapor, H2, NH3, C n H 2n+2Various gases such as hydrocarbons represented by n=n=n, ... That is, in the modification of a polyarylene sulfide-based resin film, it is preferable to introduce a molecule containing oxygen at a high partial pressure. The oxygen-containing gas is preferably contained in the introduced gas at 50 mol % or more, more preferably at 70 mol % or more. From the viewpoints of availability, stability, and prevention of excessive oxidation, the oxygen-containing gas is preferably a compound, such as CO2 or CO.
[0033] The high voltage application electrode for plasma treatment may have any shape, such as a rod shape or a plate shape with a large area, which can be used to continuously treat the film while transporting it. In addition, a magnetron electrode or a dielectric-coated electrode can be used to increase the treatment strength and reduce damage to the substrate. In particular, it is preferable to use a dielectric-coated electrode to suppress damage to the film. The counter electrode is not particularly limited as long as it can be treated by closely contacting the film, but a drum-shaped electrode that can support the film transport is preferable. The high voltage application electrode and the counter electrode do not need to be the same in number. For example, if there are two or more high voltage application electrodes for one counter electrode, the treatment efficiency can be improved while saving space. The distance between the electrodes may be appropriately set according to the gas pressure conditions and the treatment strength, but it is preferable to set it to a range of 0.05 cm to 30 cm in order to improve the adhesion of the biaxially stretched polyarylene sulfide film and suppress damage to the film.
[0034] The processing intensity is 100W·min / m 2 More than 50,000W min / m 2 It is preferable that the temperature is less than 300 W·min / m 2 More than 10,000W min / m 2 It is more preferable that the processing power density is 100W·min / m or less. The processing power density here is the value obtained by dividing the product of the power input for discharge and the time by the discharge area, and in the case of processing long films, the value obtained by dividing the input power by the width of the discharge part and the processing speed of the film. 2 From the same viewpoint, the processing power density is 300W·min / m 2 It is more preferable that the processing power density is 50,000 W·min / m or more. 2 By keeping the power density below 10,000W min / m, damage to the film can be prevented. 2 Regarding the plasma treatment conditions, when the pressure is 0.1 Pa or more and less than 10 Pa, the treatment power density is 100 W min / m2 More than 50,000W min / m 2 If the pressure is between 10 Pa and 100 Pa, the recommended value is 300 W·min / m 2 More than 10,000W min / m 2 The following is even more preferred:
[0035] The laminate is a biaxially stretched polyarylene sulfide resin film having at least one surface directly bonded to a metal foil. The metal foil preferably has a thickness of 0.05 μm or more and 30 μm or less, more preferably 0.1 μm or more and 20 μm or less. When the thickness is 0.05 μm or more, electrical conductivity can be ensured and oxidation of the metal can be suppressed. From the same viewpoint, the thickness is more preferably 0.1 μm or more. When the thickness is 30 μm or less, the metal foil becomes flexible and cracks can be suppressed from occurring and the laminate can be prevented from warping. From the same viewpoint, the thickness is more preferably 20 μm or less. The metal foil may be a single layer or two or more layers may be laminated.
[0036] The metal foil is preferably mainly composed of copper. The term "main component" refers to a component atom being 60 at% or more. Copper as the main component is preferable because it has a low conductor resistance and can reduce transmission loss. It is also advantageous for pattern formation in post-processing, and is economically useful.
[0037] The ten-point average roughness RzJIS of at least one surface of the metal foil is preferably 0.05 μm to 2.0 μm, more preferably 0.07 μm to 1.0 m. The ten-point average roughness RzJIS is defined in JIS B 0601-2001. The metal foil is a transmission path for electrical signals, and it is essential to reduce the resistance. If the surface roughness of the metal foil becomes large, the resistance increases due to the skin effect, especially in high-frequency communication, and the conductor loss increases. Since the conductor loss can be reduced by making the metal foil smooth, the roughness of the metal foil surface, i.e., the ten-point average roughness RzJIS, is preferably 2.0 μm or less. On the other hand, if the ten-point average roughness RzJIS is 0.05 μm or more, it is preferable because the adhesion with the film can be maintained and the slippage of the metal roll during processing can be adjusted.
[0038] The laminate is analyzed by TOF-SIMS on the surface (α-surface) of the metal foil peeled from the biaxially stretched polyarylene sulfide resin film that was in contact with the polyarylene sulfide resin film, and the ratio Fp / Fs of the sum of the peak intensities Fp of fragments with m / z of 79.96, 96.96, and 155.99 and the sum of the peak intensities Fs of fragments with m / z of 139.98 and 216.00 among the negative secondary metal ions obtained at the interface region between the attached resin and the metal is 1.0 or more and 10.0 or less. The α-surface can be obtained by fixing the laminate cut into a strip with a width of 5 mm and a length of 10 cm to a flat plate on the polyarylene sulfide resin film side, and peeling it at an angle of 180° at a peeling speed of 100 mm / min in an environment of room temperature of 23°C and relative humidity of 50%. The α-face obtained was etched under the following conditions and measured. Among the fragments derived from the resin, the fragment with m / z=139.98 (C6H4S2 - The position where the peak intensity of the resin-metal interface is half is defined as the interface between the resin and the metal. If there are multiple points where the peak intensity is half, the average value of those measurement data is used.
[0039] <Measurement conditions> Measurement equipment: ION-TOF time-of-flight secondary ion mass spectrometer TOF.SIMS5 Etching ion species: Cs + Etching ion acceleration energy: 1kV Primary ion species: Bi3 ++ Primary ion acceleration voltage: 25 kV Static neutralization: yes Secondary ion (detection ion) polarity: negative
[0040] The fragments assigned to Fp / Fs of the α-surface are the same as those of the film surface described above, and based on the resin composition and molecular weight, m / z=79.96 is SO3 - , m / z=96.96 is SO4H - , m / z=155.99 is C6H4SO3 - m / z=139.98 is derived from C6H4S2 - , m / z=216.00 is C 12 H8S2 - It is presumed that the origin of the above is the sulfur oxide. In other words, the first three types of ions have a structure in which the sulfur part of the polyarylene sulfide structure is oxidized, and the latter two types of ions have no oxygen atoms, and the resin is not oxidized. Setting Fp / Fs in the above range indicates that the surface of the biaxially stretched polyarylene sulfide resin film is modified with functional groups mainly consisting of sulfur oxides, and the structure is likely to have strong adhesion to the metal foil. Fp / Fs is preferably 1.0 to 10.0, more preferably 3.5 to 8.0. By setting Fp / Fs to 1.0 or more, sulfur oxides that interact with the metal foil are generated, and strong adhesion can be obtained between the smooth film and the metal foil without using an adhesive. Setting Fp / Fs to 10.0 or less can suppress weakening due to excessive oxidation of the film surface, and maintain strong adhesion to the metal foil.
[0041] The laminate can be obtained by directly bonding a metal foil to a surface-treated biaxially oriented polyarylene sulfide-based resin film. The biaxially oriented polyarylene sulfide-based resin film is heated at 100 W·min / m under an atmosphere of pressure between 0.1 Pa and 100 Pa.2 More than 50,000W min / m 2 It is preferable to perform plasma treatment at the following treatment power density, and to perform thermal lamination so that the metal foil is in direct contact with the biaxially stretched polyarylene sulfide film. Direct bonding of the metal foil and the film is preferable because it is not affected by the electrical properties of other compositions such as adhesives, and the properties of the biaxially stretched polyarylene sulfide film having low dielectric properties can be fully exhibited. In addition, by not using an adhesive, it is preferable to suppress deterioration of heat resistance and curling due to differences in thermal properties between layers.
[0042] The biaxially stretched polyarylene sulfide resin film and the metal foil can be thermally laminated by selecting a known method, such as lamination while conveying in a roll form, lamination with a plate-shaped press machine, etc. The temperature of the thermal lamination is preferably Tm-150°C or more and Tm+50°C or less, and more preferably Tm-20°C or more and Tm+30°C or less, when the melting point of the surface layer of the polyarylene sulfide resin film is Tm. By setting the temperature of the thermal lamination at Tm-150°C or more, the resin on the film surface can be softened to obtain sufficient adhesion. From the same viewpoint, the temperature is preferably Tm-20°C or more. In addition, by setting the temperature at Tm+50°C or less, the functional groups of the polyarylene sulfide resin film can be prevented from penetrating into the inner layer or being lost through mutual reaction, and the surface state can be maintained, which is preferable, since it can prevent the film from becoming brittle due to decomposition or crosslinking of the resin, resulting in a decrease in flexibility, loss of orientation, and susceptibility to cohesive failure. From the same viewpoint, the temperature is more preferably Tm+30° C. or lower.
[0043] The pressure for lamination is preferably 0.1 MPa or more and 12 MPa or less, and more preferably 0.5 MPa or more and 10 MPa or less. By setting the pressure at 0.1 MPa or more, the metal and the film can be sufficiently contacted and bonded together. From the same viewpoint, the pressure is more preferably 0.5 MPa or more. Furthermore, by setting the pressure at 12 MPa or less, deformation of the film can be suppressed and defects such as flow of the resin during lamination can be avoided. From the same viewpoint, the pressure is more preferably 10 MPa or less.
[0044] The laminate preferably has an adhesion strength between the biaxially oriented polyarylene sulfide resin film and the metal foil of 4 N / cm or more, more preferably 5 N / cm or more. There is no particular upper limit, but when it reaches substantially about 10 N / cm, measurement becomes difficult due to destruction or the like. When the adhesion strength is 4 N / cm or more, it is preferable because defects due to peeling are unlikely to occur during pattern processing, fine line processing is possible, and peeling and swelling are suppressed even during high-temperature processes such as reflow.
[0045] The laminate preferably has an insertion loss of less than 2 dB at 6 GHz measured using a microstrip line with a line length of 10 cm and an impedance of 50 Ω. The insertion loss is represented by the value of S21 described in the examples. In S21, a negative value means loss, and the absolute value of S21 is the magnitude of the loss. For example, no loss is 0 dB, and between -1 dB and -2 dB, -2 dB indicates a larger loss. An insertion loss of less than 2 dB means that the S21 value is between 0 dB and -2 dB. An insertion loss of less than 2 dB is preferable because signals can be transmitted without attenuation and the transmission characteristics are good.
[0046] The metal laminate has good adhesion between the metal foil and the polyarylene sulfide resin film, and the metal foil surface is very smooth, so it can be suitably used for circuit boards, touch panels, etc. For example, in the case of a circuit board, the metal foil is patterned to form a wiring circuit. The wiring circuit can be formed by a known method such as a subtractive method or a semi-additive method, but when the wiring width of the circuit is narrow, the semi-additive method is more preferred because the reduction in wiring width due to etching is less. In addition, the circuit board may be a single-layer board using one laminate of the present invention, or a multi-layer board may be formed by stacking multiple laminates. EXAMPLES
[0047] The present invention will be described below based on examples. Note that the present invention is not limited to these examples, and these examples can be modified or changed based on the spirit of the present invention, and they are not excluded from the scope of the present invention.
[0048] [Evaluation method] (1) Film melting point measurement The melting point of the film was measured according to JIS K7121-1987. When measuring the film of the laminate, the bonded metal foil was peeled off or etched off to remove it before measurement. Using a Seiko Instruments Inc. DSC (RDC220) as a differential scanning calorimeter and a Seiko Instruments Inc. Disk Station (SSC / 5200) as a data analyzer, 5 mg of the film was heated from room temperature to 350°C at a heating rate of 20°C / min on an aluminum tray (1st Run). The sample was taken out and quenched, and then heated from room temperature to 350°C at a heating rate of 20°C / min (2nd Run). The peak temperature of the endothermic peak of melting confirmed in the DSC chart of the obtained 2nd Run was taken as the melting point (Tm).
[0049] (2) Analysis of film surface by time-of-flight secondary ion mass spectrometry (TOF-SIMS) The TOF-SIMS analysis was performed under the following conditions: Measurement equipment: ION-TOF time-of-flight secondary ion mass spectrometer TOF.SIMS5 Primary ion species: Bi3 ++ Primary ion acceleration voltage: 25 kV Static neutralization: yes Secondary ion (detection ion) polarity: negative
[0050] From the measurement results obtained, the sum of the peak intensities of the fragments with m / z of 79.96, 96.96, and 155.99, Fp, and the sum of the peak intensities of the fragments with m / z of 139.98 and 216.00, Fs, were determined, and the ratio thereof, Fp / Fs, was calculated.
[0051] (3) Analysis of film surface by X-ray photoelectron spectroscopy (XPS) The analysis by XPS method was carried out under the following conditions: Measurement equipment: ESCALAB220iXL manufactured by Thermo Fisher Scientific Co., Ltd. Excited X-ray: monochromatic Al Kα 1,2 Rays (1486.6eV) X-ray length: 1mm Photoelectron escape angle: 90° (inclination of detector relative to sample surface) Smoothing: 11-point smoothing Horizontal axis correction: C1s(CH x , CC) was set to 284.6 eV. Measurement locations and number of times: The surface of the polyarylene sulfide resin film was measured randomly at 10 locations, each measured once, and the component ratio was calculated for each measurement. If the calculated component ratio was below the detection limit, it was recorded as 0. The arithmetic average of the component ratios at the 10 locations was regarded as the measurement result.
[0052] (3) Measurement of surface roughness of films and metal foils The ten-point average roughness RzJIS of films and metal foils is defined in JIS B0601-2001 and was measured under the following conditions: When measuring the surface roughness of a laminate, the film and metal foil are peeled off and each surface is measured. Measurement equipment: Surfcorder ET4000A manufactured by Kosaka Laboratory Co., Ltd. Stylus tip R: 2μm Measurement area: 500μm x 500μm
[0053] (4) Measurement of the dielectric constant of the film The film was stored for 24 hours or more at a temperature of 25°C and a relative humidity of 50% to eliminate the effects of humidity, and then measurements were made using the cavity resonator perturbation method at a frequency of 10 GHz, a temperature of 25°C and a relative humidity of 50%, using an Agilent Technologies network analyzer E8361A and a cavity resonator. When measuring from a metal laminate, the metal foil was removed by peeling or etching, and the resin film was left as it was, and then measurements were made.
[0054] (5) Analysis of the α-surface peeled off from a metal laminate by TOF-SIMS The α-plane was analyzed by TOF-SIMS under the following conditions: First, the laminate was cut into a rectangular shape with a width of 5 mm and a length of 10 cm, and the polyarylene sulfide resin film side was fixed to a flat plate. In an environment of room temperature of 23°C and relative humidity of 50%, the metal foil was held and peeled at an angle of 180° at a peeling speed of 100 mm / min to obtain the α-face. The obtained α-face was measured while etching under the following conditions, and the fragment (C6H4S2 - The position where the peak intensity of the metal-resin bond (presumed to be derived from the resin) becomes half was defined as the interface between the attached resin and the metal. If there are multiple points where the peak intensity becomes half, the average value of the measurement data before and after those points was used.
[0055] <Measurement conditions> Measurement equipment: ION-TOF time-of-flight secondary ion mass spectrometer TOF.SIMS5 Etching ion species: Cs + Etching ion acceleration energy: 1kV Primary ion species: Bi3 ++ Primary ion acceleration voltage: 25 kV Static neutralization: yes Secondary ion (detection ion) polarity: negative
[0056] From the measurement results, the sum of the peak intensities Fp of the fragments with m / z of 79.96, 96.96, and 155.99 at the interface between the attached resin and the metal, and the sum of the peak intensities Fs of the fragments with m / z of 139.98 and 216.00 were determined, and the ratio Fp / Fs between them was calculated.
[0057] (6) Measurement of adhesion of metal foil In the adhesion measurement of the metal foil, the thickness of the metal foil was standardized to 10 μm. When the thickness of the metal foil of the metal laminate was less than 10 μm, it was electrolytically copper plated, and when it exceeded 10 μm, the thickness was adjusted by etching or polishing.
[0058] The metal laminate was masked with 5 mm wide masking tape and etched with ferric chloride to obtain a measurement sample with a width of 5 mm and a length of 100 mm. The sample was fixed to a SUS plate with adhesive tape, and the metal foil was held to measure adhesion under the following conditions. If metal foil was bonded to both sides of the laminate, the metal foil on the non-measurement side was peeled off or etched away while protecting the measurement surface to avoid damage, and then the measurement surface was processed. Measurement equipment: Kyowa Interface Science Co., Ltd. Adhesion and film peeling analysis equipment VPA-2 Sample width: 5mm Sample length: 100mm Peeling conditions: 90°, 100mm / min Measurement distance: 75mm
[0059] From the obtained measurement profile, the average value of the adhesion strength between peel distances of 4 mm and 50 mm was taken as the adhesion strength of the metal foil.
[0060] (7) Heat resistance evaluation of laminate A 50mm x 50mm laminate was dipped in a solder bath at 260°C for 10 seconds and its deformation was evaluated. Those that maintained their size and flatness at the time of immersion were rated as ○ (good), and those that showed deformation of the surface or blistering were rated × (bad).
[0061] (8) Insertion loss measurement The laminate was processed into a single-ended microstrip line with a line length of 100 mm and impedance of 50 Ω, and measurements were performed. Measurements were performed using an Agilent Technologies 4-port vector network analyzer (E8464B, S-parameter test set N4420B) and a Cascade Microtech transmission characteristic prober system (GSG type). S21 was obtained from the S-parameter measurement, and the value at 6 GHz was read as the insertion loss. Note that a negative value for S21 means loss, and the absolute value of S21 is the magnitude of loss. For example, 0 dB means no loss, and -2 dB means that the loss is greater than -1 dB. Note that the microstrip line has a structure in which copper foil, laminate, and copper line are layered in that order.
[0062] [Example 1] Both sides of a 100 μm-thick biaxially oriented PPS film (Toray Industries, Inc. "TORELINA" (registered trademark) film #100-3A30, surface layer melting point 280°C) were treated with plasma in a CO2 atmosphere to produce a biaxially oriented polyarylene sulfide resin film. The treatment conditions were a pressure of 30 Pa, output of 500 W, and treatment power density of 1,800 W min / m. 2 It was decided.
[0063] Copper foil was thermally laminated on both sides of the plasma-treated film to obtain a metal laminate consisting of copper / biaxially oriented PPS film / copper. The copper foil used was ultra-low roughness, non-roughened electrolytic copper foil CF-T9DA-SV, 10μm thick, RzJIS0.85μm, manufactured by Fukuda Metal Foil and Powder Co., Ltd. The thermal lamination conditions were 260℃, 8MPa, and 5 minutes, using a vacuum test press KVHC-II manufactured by Kitagawa Seiki Co., Ltd., and both sides were laminated simultaneously.
[0064] [Example 2] A biaxially oriented polyarylene sulfide resin film and a laminate were obtained in the same manner as in Example 1, except that the plasma treatment was performed under a pressure of 10 Pa.
[0065] [Example 3] The plasma treatment conditions were: output 1,250 W, treatment power density 4,500 W min / m 2 A biaxially oriented polyarylene sulfide resin film and a laminate were obtained in the same manner as in Example 1, except that the above-mentioned was used.
[0066] [Example 4] A biaxially oriented polyarylene sulfide resin film and a laminate were obtained in the same manner as in Example 1, except that a 100 μm-thick biaxially oriented PPS film having a surface layer melting point of 255° C. was subjected to plasma treatment and the pressing temperature was set to 240° C.
[0067] [Example 5] A biaxially stretched polyarylene sulfide resin film and a laminate were obtained in the same manner as in Example 1, except that the copper foil was laminated using a roll laminator. The copper foil lamination conditions were a pressure of 0.7 MPa, a temperature of 270° C., and a conveying speed of 1 m / min. [Example 6] A biaxially stretched polyarylene sulfide resin film and a laminate were obtained in the same manner as in Example 1, except that the copper foil used was JXEFL-V2 electrolytic copper foil for flexible printed circuit boards manufactured by JX Metals Corporation, having a thickness of 12 μm and RzJIS of 1.6 μm.
[0068] [Comparative Example 1] Both sides of a 50 μm-thick polyimide film (Toray DuPont Co., Ltd.'s "Kapton" (registered trademark) film 200EN, no melting point) were plasma-treated in an O2 atmosphere. The treatment conditions were a pressure of 30 Pa, an output of 500 W, and a treatment power density of 1,800 W min / m. 2 Copper was sputtered onto the obtained film to form a seed layer, and copper plating was performed to a metal thickness of 10 μm to obtain a laminate.
[0069] [Comparative Example 2] A polyarylene sulfide resin film and a laminate were obtained in the same manner as in Example 1, except that an unstretched film obtained by melt extruding and quenching a polyphenylene sulfide resin consisting of p-phenylene sulfide units was used.
[0070] [Comparative Example 3] A biaxially oriented polyarylene sulfide resin film and a metal laminate were obtained in the same manner as in Example 1, except that the plasma treatment was not performed and a metal was laminated.
[0071] [Comparative Example 4] A biaxially oriented polyarylene sulfide resin film and a laminate were obtained in the same manner as in Example 3, except that the plasma treatment was performed under an Ar atmosphere.
[0072] The evaluation results for each Example and Comparative Example are shown in Tables 1 and 2. In Examples 1 to 6, generally good values were obtained for adhesion, heat resistance, and insertion loss. On the other hand, the polyimide in Comparative Example 1 had no fragment corresponding to Fs, so there was no Fp / Fs value. The polyimide had a high relative dielectric constant, so the insertion loss was large. The unstretched PPS in Comparative Example 2 had poor heat resistance and was unstretched and had large thickness unevenness, so impedance matching was not achieved and the loss was large. In Comparative Examples 3 and 4, the adhesion of the metal foil was poor, and the line for measuring insertion loss could not be processed, so measurement was not possible.
[0073] [Table 1]
[0074] [Table 2] [Industrial Applicability]
[0075] The biaxially oriented polyarylene sulfide resin film and laminate according to the present invention can be widely used for wiring boards, circuit materials, etc. used in the information and communications field. [Explanation of symbols]
[0076] 1: Polyarylene sulfide resin film 2: Metal foil 3: α surface
Claims
1. A biaxially stretched polyarylene sulfide resin film, characterized in that the ratio Fp / Fs of the sum of peak intensities Fp of fragments having ratios m / z of mass m to charge number z of 79.96, 96.96, and 155.99, respectively, among negative secondary ions obtained when at least one surface is analyzed by time-of-flight secondary ion mass spectrometry (TOF-SIMS), to the sum of peak intensities Fs of fragments having ratios m / z of 139.98 and 216.00, respectively, is 1.0 or more and 10.0 or less.
2. 2. The biaxially stretched polyarylene sulfide resin film according to claim 1, wherein the ratio O / C of the number of oxygen atoms to the number of carbon atoms obtained by analyzing at least one surface by X-ray photoelectron spectroscopy (XPS) is 0.1 or more and 0.3 or less.
3. 3. The biaxially stretched polyarylene sulfide resin film according to claim 1, wherein at least one surface has a ten-point average roughness Rz JIS of 0.05 μm or more and 3.0 μm or less.
4. The biaxially oriented polyarylene sulfide resin film according to claim 1 or 2, having a melting point of 260° C. or higher.
5. 3. The biaxially stretched polyarylene sulfide resin film according to claim 1, which has a relative dielectric constant of 3.2 or less at a frequency of 10 GHz.
6. A laminate having a metal foil bonded to at least one surface of a biaxially oriented polyarylene sulfide resin film, characterized in that, when the surface (α-surface) of the metal foil peeled off from the biaxially oriented polyarylene sulfide resin film that was in contact with the biaxially oriented polyarylene sulfide resin film is analyzed by time-of-flight secondary ion mass spectrometry (TOF-SIMS), among negative secondary metal ions obtained at the interface between the attached resin and the metal, the ratio Fp of the sum of peak intensities of fragments having ratios m / z of mass m to charge number z of 79.96, 96.96, and 155.99, respectively, to the sum of peak intensities Fs of fragments having ratios m / z of 139.98 and 216.00, respectively, is 1.0 or more and 10.0 or less.
7. The laminate according to claim 6 , wherein the biaxially oriented polyarylene sulfide resin film and the metal foil are adhered to each other with an adhesion strength of 4 N / cm or more.
8. The laminate according to claim 6 or 7, wherein the biaxially stretched polyarylene sulfide resin film has a melting point of 260° C. or higher.
9. 8. The laminate according to claim 6, wherein the main component of the metal foil is copper.
10. The laminate according to claim 6 or 7, wherein the ten-point average roughness Rz JIS of the surface of the metal foil is 0.05 μm or more and 2.0 μm or less.
11. 8. The laminate according to claim 6, wherein the laminate is processed into a microstrip line having a line length of 10 cm and an impedance of 50 Ω, and in high-frequency circuit characteristics measured at a frequency of 6 GHz, the insertion loss is less than 2 dB.
12. A circuit board comprising the laminate according to claim 6 or 7.
13. A method for producing a biaxially stretched polyarylene sulfide-based resin film in which a ratio Fp / Fs of a sum of peak intensities Fp of fragments having ratios m / z of mass m to charge number z of 79.96, 96.96, and 155.99, respectively, among negative secondary ions obtained when at least one surface is analyzed by time-of-flight secondary ion mass spectrometry (TOF-SIMS), to a sum of peak intensities Fs of fragments having ratios m / z of 139.98 and 216.00, respectively, is 1.0 or more and 10.0 or less, the method comprising the steps of: subjecting the biaxially stretched polyarylene sulfide-based resin film to a vacuum plasma treatment in an oxygen-containing gas atmosphere.
14. a plasma treatment step of subjecting the biaxially stretched polyarylene sulfide-based resin film to a vacuum plasma treatment in an oxygen-containing gas atmosphere; A method for producing a laminate, comprising: a bonding step of overlapping a surface of the vacuum plasma-treated biaxially stretched polyarylene sulfide resin film with a metal foil, and bonding the surfaces by heating and pressing the surfaces, A method for producing a laminate, characterized in that, when the surface (α-surface) of the metal foil peeled off from the biaxially oriented polyarylene sulfide resin film that was in contact with the biaxially oriented polyarylene sulfide resin film is analyzed by time-of-flight secondary ion mass spectrometry (TOF-SIMS), among the negative secondary metal ions obtained at the interface between the attached resin and the metal, the ratio Fp of the sum of peak intensities of fragments having ratios m / z of mass m to charge number z of 79.96, 96.96, and 155.99, respectively, to the sum of peak intensities Fs of fragments having ratios m / z of 139.98 and 216.00, respectively, is 1.0 or more and 10.0 or less.
15. a plasma treatment step of subjecting the biaxially stretched polyarylene sulfide-based resin film to a vacuum plasma treatment in an oxygen-containing gas atmosphere; A method for producing a laminate, comprising a step of overlapping a surface of the vacuum plasma-treated biaxially stretched polyarylene sulfide resin film with a metal foil, and bonding the surfaces by heating and pressing, A method for producing a laminate, characterized in that, in the high-frequency circuit characteristics measured by processing the laminate into a microstrip line having a line length of 10 cm and an impedance of 50 Ω, an insertion loss at a frequency of 6 GHz is less than 2 dB.
Citation Information
Patent Citations
Wiring board and manufacturing method thereof
JP2006179609A
Original board for printed wiring board and printed wiring board
JP2018110193A
Laminate and method for manufacturing the same
JP2020199707A